Geography Teachers, Reflexivity, and Geomedia. The Construction of an Empirically-Based Typology - Gryl, Inga (Journal of Geography Education, 2012)
Spatial information and decisions are increasingly modeled with the help of geomedia. Likewise the access to geomedia and tools for geomedia production is democratized as part of the web2.0. Thus, reflexive geomedia competence is a fundamental skill for everyday life. Reflexive geomedia competence is the critical consumption of geomedia and the awareness of the social construction of spaces displayed in geomedia, while being self-reflexive towards one's own performance with geomedia as well. Basing on an interview study conducted by the author this paper answers the question, if secondary school teachers are able and willing to promote reflexive geomedia competence in geography education at school and how this ability and willingness can be supported. The results indicate that the implementation of reflexive geomedia competence in education is closely linked to the teachers' general willingness to critical thinking and pedagogical reflexivity. The data leads to a typology of teachers, ranging from high reflexivity to complete aversion to reflection regarding the usage of geomedia. These types point to different opportunities to further reflexive geomedia competence at school.
Keywords: geomedia, reflection, reflexive geomedia competence, teacher competences, typology, qualitative research